Immune monitoring of trabectedin therapy in refractory soft tissue sarcoma patients - the IMMUNYON study - Rodrigues-Santos, Paulo; Almeida, Jani Sofia; Sousa, Luana Madalena; Couceiro, Patrícia; Martinho, António; Rodrigues, Joana; Fonseca, Ruben; Santos-Rosa, Manuel; Freitas-Tavares, Paulo; Casanova, José Manuel (Frontiers in Immunology, 2025)
Soft tissue sarcomas (STS) encompass over 50 histologic subtypes, representing more than 1% of solid tumors. Standard treatments include surgical resection and therapies such as anthracyclines or trabectedin for advanced cases, though challenges persist due to the tumor microenvironment’s complexity and limited immune profiling data. This study evaluates Trabectedin therapy in 22 refractory STS patients, analyzing progression-free survival (PFS) and immune responses. Immune monitoring included deep immunophenotyping (200+ parameters), gene expression profiling (103 genes), and soluble proteome analysis (99 analytes). Using RECIST1.1 criteria, 68.2% of patients achieved stable disease (SD), while 31.8% exhibited progression disease (PD). Therapy duration revealed 59.1% treated for less than 12 months (<12M) and 40.9% for 12 or more months (≥12M). A significant PFS improvement was observed in SD versus PD patients (p=0.0154), while therapy duration showed no effect (p=0.5433). PD patients showed reduced eosinophils (p<0.05) and Th2 cells (p<0.05). Gene expression analysis identified changes in BTRC (decreased), IFNA1 (increased), and IL9 (increased) in PD versus SD patients (p<0.05). Patients treated ≥12M exhibited increased activated HLA-DR Th2 cells (p<0.05) and decreased exhausted B cells and NK cell subsets (p<0.05). Principal component and hierarchical clustering analyses identified distinct immune profiles associated with RECIST1.1 and therapy duration, underscoring immune profiling’s role in understanding treatment responses. These findings support further research into immune monitoring for future clinical trials.